Effect of vertical air motion on disdrometer derived Z-R coefficients - Michaelides, Silas; Lane, John E.; Kasparis, Takis (My University, 2019)
For synoptic-scale motions the vertical velocity component is typically of the order of a few centimeters per second. In general, the vertical velocity is not measured directly but must be inferred from other meteorological fields that are measured directly. In the present study, a Joss-Waldvogel disdrometer was used in order to establish the drop size distributions (DSD) at Athalassa, Cyprus. Data from a radiosonde station co-located with the disdrometer were also collected which were subsequently used to derive estimates of vertical velocities. Meteorological fields, including vertical velocities, were extracted from an atmospheric reanalysis, for an area centered over the disdrometer and radiosonde station instrumentation. The disdrometer data were used to determine the Z-R disdrometer derived coefficients, A and b, where Z = A R b . To model the vertical air effect on the Z-R disdrometer derived coefficients an idealistic notion of flux conservation of the DSD is adopted. This adjusted DSD (FCM-DSD) is based on the exponential DSD and is modified by the relationship between drop terminal velocity (D) and vertical air speed w. The FCM-DSD has a similar appearance to the popular gamma DSD for w < 0. A clear segregation is seen in the A-w plane for both data and model. The data points are also clearly segregated in the b-w plane, but the model points are on opposite sides of the w = 0 line. It is also demonstrated that vertical velocities can be extracted from radiosonde data if initial balloon volume is accurately measured, along with an accurate measurement of the mass of the complete radiosonde-balloon system. To accomplish this, vertical velocities from radiosonde data were compared to reanalysis vertical velocity fields. The resulting values of initial balloon volume are found to be within the range of measured values.
Keywords: Drop size distribution; ECMWF; ERA-Interim; Joss-Waldvogel disdrometer; Radiosonde; Reanalysis; Vertical velocity